Evaluation in EFL written stories (Categories and Units in Language and Linguistics, 2020)
The structure of oral narratives, as studied by Labov & Waletzky (1967) involves an abstract, orientation, complicating action, resolution, evaluation and coda. Narratives are presented on TV and radio news, newspapers as well as in everyday conversations (Ervin- Tripp & Küntay, 1997), also during children’s dramatic play (Ervin-Tripp & Küntay, 1997), jokes (Badio, 2020), stories as rehearsal for action (Kiełkiewicz-Janowiak, 2015), stories as background of the meaning of lexical items, e.g. dirty money (Filar, 2015), advertisements and in a great number of other contexts. The different components of narratives as listed by Labov & Waletzky (1967) include the complex category of evaluation. Characterisation and discussion of this unit of narrative constitutes the goal of the present article.